2000
DOI: 10.1007/s001090000153
|View full text |Cite
|
Sign up to set email alerts
|

Elevated p21 mRNA level in skeletal muscle of DMD patients and mdx mice indicates either an exhausted satellite cell pool or a higher p21 expression in dystrophin-deficient cells per se

Abstract: Abnormalities in proliferation and differentiation of the dystrophin-deficient muscle are a controversial aspect of the pathogenesis of Duchenne muscular dystrophy (DMD). Analyses of molecules involved in cell cycle modulation do not exist in this context. Cells withdrawn from the cell cycle permanently express p21. The fact that p2 1, in contrast to other cell cycle proteins, is not diminished when myotubes are reexposed to growth media, allocates this cyclin-dependent kinase inhibitor a special function. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…11,71,72 In parallel to fusion with host fibers and dystrophin recovery, MuStem cells generated satellite cells, an essential feature in the context of satellite cell pool exhaustion in muscular dystrophy. 73,74 This data suggested that MuStem cell injection could have a long-term impact on the regenerative potential of dystrophic fibers by their constant recruitment for the host fiber regeneration. Similar contribution to the satellite cell pool has been demonstrated in injured mouse muscles for muscle SP cells, 21 muscle-derived floating populations, 42 CD133 ϩ cells, 24 and synovial membrane-derived mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 91%
“…11,71,72 In parallel to fusion with host fibers and dystrophin recovery, MuStem cells generated satellite cells, an essential feature in the context of satellite cell pool exhaustion in muscular dystrophy. 73,74 This data suggested that MuStem cell injection could have a long-term impact on the regenerative potential of dystrophic fibers by their constant recruitment for the host fiber regeneration. Similar contribution to the satellite cell pool has been demonstrated in injured mouse muscles for muscle SP cells, 21 muscle-derived floating populations, 42 CD133 ϩ cells, 24 and synovial membrane-derived mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 91%
“…JunB has been shown to increase skeletal muscle hypertrophy and mass by promoting FoxO3 binding to Fbxo32 and MuRF1 promoters and thereby reduces protein breakdown (68). The cyclindependent kinase inhibitor p21 (Cdkn1a), which plays an important role in skeletal muscle regeneration (20,33), was also significantly elevated in BCATm KO mouse muscle (Supplementary Tables S1-S3). Interestingly, eIF4G2 (also known as death-associated protein 5, DAP-5) expression was almost twofold greater in muscle of KO compared with wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The final RNA was digested with DNase and with an RNase inhibitor added. Reverse transcription was performed simultaneously using Superscript II reverse transcriptase (Invitrogen, Carlsbad, CA) followed by the PCR reactions and preparation of serial dilutions of the purified PCR products (35). PCR primers and TaqMan fluorogenic probes were designed using the Primer Express program, version 1.01 (Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%